sPHENIX Highlights: First Results from sPHENIX at RHIC - Nouicer Rachid (EPJ Web of Conferences, 2025)
First results from the sPHENIX experiment on the π0 v2 and dET =dη in Au+Au collisions at √sNN = 200 GeV using detector commissioning data during the RHIC 2023 Run are presented. These results are shown across a large centrality range, and compared to previous PHENIX and STAR results. These measurements demonstrate the sPHENIX capabilities towards accomplishing the sPHENIX jet physics program. From the ongoing RHIC 2024 Run, p + p collisions at √s = 200 GeV, a first glimpse of the measurements KS0 and Λ0 obtained by the sPHENIX Time Projection Chamber (TPC) detector are shown.